Enhanced Stability of Perovskite Solar Cells Incorporating Dopant‐Free Crystalline Spiro‐OMeTAD Layers by Vacuum Sublimation. Issue 2 (4th November 2019) - Barranco, Angel; Lopez‐Santos, Maria C.; Idigoras, Jesus; Aparicio, Francisco J.; Obrero‐Perez, Jose; Lopez‐Flores, Victor; Contreras‐Bernal, Lidia; Rico, Victor; Ferrer, Javier; Espinos, Juan P.; Borras, Ana; Anta, Juan A.; et al.
Abstract: The main handicap still hindering the eventual exploitation of organometal halide perovskite‐based solar cells is their poor stability under prolonged illumination, ambient conditions, and increased temperatures. This article shows for the first time the vacuum processing of the most widely used solid‐state hole conductor (SSHC), i.e., the Spiro‐OMeTAD [2, 2′, 7, 7′‐tetrakis ( N, N ‐di‐ p ‐methoxyphenyl‐amine) 9, 9′‐spirobifluorene], and how its dopant‐free crystalline formation unprecedently improves perovskite solar cell (PSC) stability under continuous illumination by about two orders of magnitude with respect to the solution‐processed reference and after annealing in air up to 200 °C. It is demonstrated that the control over the temperature of the samples during the vacuum deposition enhances the crystallinity of the SSHC, obtaining a preferential orientation along the π–π stacking direction. These results may represent a milestone toward the full vacuum processing of hybrid organic halide PSCs as well as light‐emitting diodes, with promising impacts on the development of durable devices. The microstructure, purity, and crystallinity of the vacuum sublimated Spiro‐OMeTAD layers are fully elucidated by applying an unparalleled set of complementary characterization techniques, including scanning electron microscopy, X‐ray diffraction, grazing‐incidence small‐angle X‐ray scattering and grazing‐incidence wide‐angle X‐ray scattering, X‐ray photoelectron spectroscopy, and Rutherford backscattering spectroscopy. Abstract : Spiro‐OMeTAD [2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxyphenyl‐amine) 9, 9′‐spirobifluorene], the most used solid‐state hole conductor in perovskite solar cells (PSCs), is usually processed in solution, but requires dopants for efficient charge transport. Here, dopant‐free Spiro‐OMeTAD layers prepared by vacuum sublimation are reported. Temperature control of the samples during evaporation induces crystalline and microstructural changes. The implementation in PSCs demonstrates unprecedented superior stability with respect to solution‐processed devices.